ANALYSIS OF THE IMPACT OF DIGITAL ACCOUNTING TRANSFORMATION ON THE FINANCIAL EFFICIENCY OF SMALL, MICRO, AND MEDIUM ENTERPRISES (MSMES) IN INDONESIA: AN INTEGRATED MODEL - Uyun, Jamilatul; Kusuma, Nailah Aka; Rohmaniyah, Kholishotur; Lutfiyah, Lutfiyah (Universitas Bunda Mulia, 2026)
Background: Major changes in digital accounting have had a significant impact on various business sectors, especially on Micro, Small, and Medium Enterprises (MSMEs).Objective: This study aims to analyze how digital transformation in accounting can enhance financial efficiency in the Micro, Small, and Medium Enterprises (MSMEs) sector.Research Methods: This research is a quantitative study. The research data were obtained through questionnaires distributed to 602 MSME respondents. Data analysis and hypothesis testing were conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM).Research Results: The results of this study indicate that the adoption of digital accounting, FinTech innovation, and technological competition has a direct impact on enhancing financial efficiency. All pathways leading to improved financial efficiency proved significant in hypothetical tests, especially the adoption of FinTech innovations, which was highly encouraging in improving financial efficiency. Additionally, technological intelligence has an indirect impact on the relationship between the implementation of digital accounting and technological competition in enhancing financial efficiency.Originality/Novelty of Research: This in-depth research examines the concrete effect of digital transformation on accounting associated with financial Efficiency at the MSME scale, which often lags in technology application. It also develops an integrated model regarding the impact indicators of digitalization on the financial efficiency of MSMEs. For practitioners, the results of this study can provide meaningful insights for policymakers and organizations seeking to adopt digital technology to improve financial efficiency.